2021
DOI: 10.1038/s41598-021-96782-x
|View full text |Cite
|
Sign up to set email alerts
|

Renal function trajectories in hepatitis C infection: differences between renal healthy and chronic kidney disease individuals

Abstract: Associations between hepatitis C virus (HCV) and chronic kidney disease (CKD) have been reported; however, differences of renal progression between general and CKD population remain to be elucidated in prospective studies. A total of 1179 participants, who have tested for anti-HCV antibody, were enrolled and prospectively followed for 3 years. The risks associated with HCV infection, in terms of incidence of CKD, annual estimated glomerular filtration rate (eGFR) changes and 50% decline of eGFR at 3-year from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The higher drug burden on kidneys, as well as adverse drug-drug interactions 33 increase susceptibility for adverse kidney related outcomes compared to other PWH. A meta-analysis showed that sharing syringes and drug preparation materials is associated with a ~ 2 fold increase in risk of HCV seroconversion 34 , which can contribute to kidney function decline via accumulation of viral antigen–antibody complexes and viral effects 35 , 36 . This study also reported population attributable risk ranging between 25 and 43%, implying the percent by which HCV seroconversion can reduce upon elimination of these behaviors in the PWID population.…”
Section: Introductionmentioning
confidence: 99%
“…The higher drug burden on kidneys, as well as adverse drug-drug interactions 33 increase susceptibility for adverse kidney related outcomes compared to other PWH. A meta-analysis showed that sharing syringes and drug preparation materials is associated with a ~ 2 fold increase in risk of HCV seroconversion 34 , which can contribute to kidney function decline via accumulation of viral antigen–antibody complexes and viral effects 35 , 36 . This study also reported population attributable risk ranging between 25 and 43%, implying the percent by which HCV seroconversion can reduce upon elimination of these behaviors in the PWID population.…”
Section: Introductionmentioning
confidence: 99%
“…Several global surveys have shown a higher prevalence rate of HCV infection among patients on hemodialysis than among patients on peritoneal dialysis [ 11 14 ]. Apart from the mechanistic relationship, many epidemiologic studies have confirmed a strong link between HCV and CKD [ 15 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) infection had been shown to associate with chronic kidney disease (CKD) [1]. When compared with HCV seronegative individuals, those with HCV seropositivity were more likely to have dipstick proteinuria and long-term risk of incident CKD [2,3]. Additionally, among United States (U.S.) veterans with baseline estimated glomerular filtration rate (eGFR) � 60 mL/min/1.73 m 2 , those with anti-HCV antibodies or detectable HCV ribonucleic acid (RNA) were associated with higher risk of incident CKD and rapid decline in eGFR as opposed to seronegative individuals [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, among United States (U.S.) veterans with baseline estimated glomerular filtration rate (eGFR) � 60 mL/min/1.73 m 2 , those with anti-HCV antibodies or detectable HCV ribonucleic acid (RNA) were associated with higher risk of incident CKD and rapid decline in eGFR as opposed to seronegative individuals [4]. Furthermore, CKD patients with HCV seropositivity or HCV viremia had higher risk of kidney disease progression when compared with individuals without HCV infection [3,5,6].…”
Section: Introductionmentioning
confidence: 99%